The Improvement of Protein Retention through a Higher Utilization of Carbohydrate in the Diet with Chromium for Common Carp Cyprinus carpio Linn. - I. Mokoginta; F. Hapsyari; M. Agus Suprayudi (Jurnal Akuakultur Indonesia)
This experiment was conducted to improve the protein retention through carbohydrate efficiency in the chromium diet of common carp Cyprinus carpio. Four experimental diets with isonitrogen and isocaloric but different Cr+3 level 0,00; 1,33; 2,23 and 3,96 ppm were used in this experiment. Fish with body weight of 5,31 ± 0,02 gram were reared in aquaria (50 x 40 x 35 cm); 20 fish per aquarium. Fish fed upon the experimental diets three times daily, at satiation for 50 days. Results of this experiment showed that the protein retention could be improved by given Cr+3 in the diet. Based on the respon curve of protein retention (Yi = -1.1678X2 + 3,7223X + 24,818 ; R2 = 0,9) it was found that the optimum Cr*J in the diet was 1,59 ppm. The maximum relative growth rate was found at 2,16 ppm Cr3+ (Y2 = -14,592 X: + 63,18IX + 426,43 ; R = 0,9). The feed efficiency and the survival rate of the fish are the same between treatment (p>0.05). The protein level of the fish from treatment 3,96 ppm Cr+3 was lower than the others; the lipid level of Cr+3 diets was higher than that of non Cr+3 diet; however the carbohydrate level of fish from diet 2,23 Cr+3 was lower than the others. It was concluded that the optimum level of Cr +3 in the diet of common carp was 1,59-2,16 ppm